MO840: A Survey on the Impact of Pruritus Associated With Chronic Kidney Disease (CKD-AP) In the Quality of Life of Patients Undergoing Haemodialysis in Spain. (3rd May 2022) - Reyes, Victor; Caro, Johanna; Pais, Beatriz; Buades F, Juan M; De Sequera Ortiz, Patricia; Espín, Jaime; Tombás, Antonio; Moreno, Marta; Carlos Julián Mauro, Juan
Abstract: BACKGROUND AND AIMS: Chronic kidney disease (CKD) patients can be affected by pruritus. In Spain, CKD associated pruritus (CKD-aP) affects 60% of CKD patients on haemodialysis (HD). CKD-aP severely impacts in physical and mental health of patients, resulting in sleep disturbance, depressed mood, increased risk of infection and a low quality of life [1 ]. In Spain, there is a lack of data regarding CKD-aP patient's quality of life (QoL). The aim of the study is to determine how CKD-aP affects the HD patients' QoL in Spain. METHOD: The study was structured in two phases: The first phase involved the design and the validation (by a multidisciplinary panel of 9 experts) of a survey to assess CDK-aP patient's QoL. The second phase consisted in sending the survey to CKD patients and subsequent results analysis. RESULTS: The survey was structured in 10 domains with 25 questions that collected relevant aspects of the CKD-aP patients' QoL. A total of 189 HD patients answered the survey, 97 (51%) of whom had CKD-aP. The main results are showed in Table 1 . CKD-aP HD patients reported a health status significantly lower than HD patients without pruritus (mean = 46 versus 53 out of 100, respectively, P- value = 0.02). Moreover, the health status worsened when increasing severity of pruritus (mild = 51/100; moderate = 48/100; severe = 32/100). Out of 10, 6 CKD-aP patients suffer from it always or sometimes a day. A total of 30% of patients reported pruritus throughout the day, while 29% suffer from it at night. 39% of CKD-aP patients, of which 39% have severe pruritus and 62% moderate, reported having difficulty falling asleep sometimes a week or more. A total of 44% of patients experienced irritability once a week or more, 32% frustration, 21% distress, 11% depression and 7% embarrassment. In addition, pruritus limits patients' daily and social activities (12% patients were limited once a week or more), preventing them from doing sports, housework, going to restaurants and/or engaging in cultural activities. It also alters patients' cognitive function, leading to a lack of concentration and/or confusion (22% patients had an altered cognitive function once a week or more). 10% of patients had infections or fistula damage due to scratching. 62% of CKD-aP patients were not treated for pruritus, and of those treated, 47% were dissatisfied with their treatment. CONCLUSION: This study shows that CKD-aP is a distressing condition with a huge impact in CKD HD patients' QoL in Spain. However, there is an unmet need in terms of treatment, meaning that new treatments for CKD-aP are necessary to improve patients' QoL.